Empowerment of Women with Narcotic Cases - Nurhayati; Rita Komalasari; Cecep Mustafa (UIN Raden Mas Said Surakarta, 2022)
This paper for the first time presents the results of research related to the aspects of empowerment of women involved in narcotic cases. The research methods presented in this paper are in the form of literature research and field research. Two countries, Scotland and Indonesia, were included to gain various perspectives through a literature review. The results of the field research show that the empowerment of women with narcotic cases is still based on a sense of social justice. This paper contributes to ensuring equality in empowerment for women.